Numerical Simulations of Rarefied Gases in Curved Channels: Thermal Creep, Circulating Flow, and Pumping Effect (Communications in Computational Physics, 2020)
We present numerical simulations of a new system of micro-pump basedon the thermal creep effect described by the kinetic theory of gases. This device ismade of a simple smooth and curved channel with a periodic temperature distribution.Using the Boltzmann-BGK model as the governing equation for the gas flow, wedevelop a numerical method based on a deterministic finite volume scheme, implicitin time, with an implicit treatment of the boundary conditions. This method is comparativelyless sensitive to the slow flow velocity than the usual Direct Simulation MonteCarlo method in case of long devices, and turns out to be accurate enough to computemacroscopic quantities like the pressure field in the channel. Our simulations showthe ability of the device to produce a one-way flow that has a pumping effect.